2007
DOI: 10.1109/tmi.2007.895483
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Diagnostic B-Mode Ultrasonography Into CT-Based Radiation Treatment Planning

Abstract: Abstract-This paper presents methods and a clinical procedure for integrating B-mode ultrasound images tagged with position information with a planning computed tomography (CT) scan for radiotherapy. A workflow is described that allows the integration of these modalities into the clinic. A surface mapping approach provides a preregistration of the ultrasound image borders onto the patient's skin. Successively, a set of individual ultrasound images from a freehand sweep is chosen by the physician. These images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Feature based registration techniques also suffer from major difficulties encountered during the intensity based segmentation of US. There are several studies reported where MR or CT was registered either to sequence of tracked 2D US images [8,9] or to 3DUS volumes [10][11][12]. Both approaches ignore the dynamic nature of the US modality, that is, they treat the US images as static and rely on the persistence of features over time.…”
Section: Introductionmentioning
confidence: 99%
“…Feature based registration techniques also suffer from major difficulties encountered during the intensity based segmentation of US. There are several studies reported where MR or CT was registered either to sequence of tracked 2D US images [8,9] or to 3DUS volumes [10][11][12]. Both approaches ignore the dynamic nature of the US modality, that is, they treat the US images as static and rely on the persistence of features over time.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, we predicted the location of anatomical landmarks by relying on a temporal pre-therapeutical MRI sequence based on the observation of US images acquired during therapy with an average accuracy of 4.2 mm. Our performance is comparable to state-of-the-art methods (3.7 mm for multi-modal registration [11,17,6], 1.5 mm for US tracking [2,3]) while being less complex. Lowest mean errors were achieved when employing SFA.…”
Section: Resultsmentioning
confidence: 68%
“…A main challenge is to define an effective image similarity measure. For liver US images, approaches include gradient images [9], matching of extracted vessels [13,11], simulations of US from CT images [17,5] and hybrids [6]. Assuming the same breathing phase, alignments are often optimized with respect to a rigid transformation.…”
Section: Introductionmentioning
confidence: 99%
“…A study that uses US and CT (computer tomography) images of kidneys is described in [16], where the registration is carried out by minimizing a correlation ratio (CR) between the images pre-processed to remove noise and enhance edges. There are also registrations that use US and CT images in different organs, such as in [17], where images of head and neck are registered using a multi-component similarity measure involving weighted MI, intensities and edge maps. Another example using CT images is [18], in which US images of liver and kidney are registered with CT by a method that simulates US images using the CT data, and then registers the US image applying a similarity measure between it and the simulation.…”
Section: Introductionmentioning
confidence: 99%